Metformin Increases Serum Isthmin-1 Levels and Lowers Low-Density Lipoprotein: Potential Implications for Lipid Metabolism in T2DM - Bozoglan, Merve Yilmaz; Kuloglu, Tuncay; Gozel, Nevzat; Kilinc, Faruk; Cakmak, Erkan; Akkoc, Ramazan Fazil; Dagoglu Hark, Betul (Mdpi, 2025)
Background and Objectives: Type 2 Diabetes Mellitus (T2DM) is a metabolic disease caused by the failure of the skeletal muscle, liver and adipose tissue to respond to insulin. Metformin is the first choice for the treatment of T2DM. Isthmin 1 (Ism1) is a newly discovered adipokine that affects all carbohydrate, lipid and protein metabolism. This study examines the changes in serum and salivary levels of Ism1 in patients using metformin, considering its potential as a follow-up marker for T2DM if present in the salivary glands. Materials and Methods: The study included 30 newly diagnosed T2DM patients and 30 non-diabetic controls. Ism1 was measured by ELISA in serum and saliva after 3 months and compared with routine biochemical parameters. Immunostaining of Ism1 was performed in salivary glands. Results: Ism1 was immunohistochemically detected in salivary glands for the first time. Serum Ism1 levels increased significantly after 3 months of metformin treatment (p = 0.028). The increase in salivary Ism1 levels did not reach statistical significance. Fasting plasma glucose (FPG) (p < 0.001), HbA1c (p < 0.001) and LDL (p = 0.015) levels decreased with metformin. There was a significant negative correlation between the increase in Ism1 levels and the decrease in LDL levels (rho = -0.362, p = 0.05). Conclusions: Despite its first detection in salivary glands, the hypothesis that Ism1 may be a surveillance marker in T2DM could not be confirmed. The negative correlation of Ism1 with LDL levels suggests that Ism1 may contribute to the ameliorative effect of metformin on serum lipids. Further studies are needed to support this conclusion.
Keywords: adipokine; isthmin 1; metformin; T2DM; LDL